Master Class with Joyce DiDonato at Carnegie Hall (II/III) 2019 Resnick Education Wing - Bellini, Vincenzo 1801-1835; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Verdi, Giuseppe 1813-1901 (Carnegie Hall, 2019)
Joyce DiDonato returns to Carnegie Hall for yet another series of master classes! Celebrated the world over for her heartfelt and captivating performances, the mezzo-soprano is a sensitive and generous teacher with years of experience and a large repertoire, all of which she shares here with promising young opera singers. Joyce DiDonato appears courtesy of Warner Classics. Photo : © Chris Lee
Keywords: Singing; Operas; Singing -- Instruction and study; Operas -- Excerpts, Arranged; masterclass; Songs; Instructional and educational works; Dramatic music; Internet videos